KEBERADAAN PT. TRI BAKTI SARIMAS TERHADAP KEADAAN SOSIAL DAN EKONOMI MASYARAKAT DI DESA PANTAI KABUPATEN KUANTAN SINGINGI (1995-2018) - Dizi Papila Pertiwi; Isjoni Isjoni; Bedriati Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrack: The development of oil palm plantations has a dual impact on the regional economy especially in creating employment opportunities. The development of oil palm plantations has provided benefits so that it can expand the power of distributions to the surronding community. So that the development of oil palm plantations is increasingly felt the impact on workers working in the plantation sector, the impact can be seen from the increase in additional income. The purpose of this study is 1) to determine the background of the establishment process of PT. Tri Bakti Sarimas in Pantai Village, Kuantan Singingi Regency 2) to find out how the socio-economic conditions of Desa Pantai community before and after the establishment of PT. Tri Bakti Sarimas in Pantai Village, Kuantan Singingi Regency 3) to find out the business that was carried out by PT. Tri Bakti Sarimas on the socio-economic community in Pantai Desa Kuantan Singingi. In this method using qualitative and quantitative methods where this will provide complete information that is useful for science. The results of this study that the coastal village community of Kuantan Singingi Regency (1995-2018) experienced a development in the socio-economic field which was influenced by the establishment of PT. Tri Bakti Sarimas with an effort / program of concern for the Pantai Desa community, namely Corporate Social Responsibility (CSR).Key Words: PT. Tri Bakti Sarimas Kuantan Singingi Regency, Social Economy